Modele pamięci o Holokauście na Ukrainie w kontekście marginalności i marginalizacji dyskursów pamięci - Jędraszczyk, Katarzyna (My University, 2021)
There are two main models of memory in Ukraine: nationalist and post-Soviet. After 1991, Ukrainian historiography concerning the Holokaust was influenced by Soviet and emigration historiography. It was reactive to the allegations that the Ukrainians are anti-Semitic. In the nationalist model of memory, there is no space for the memory of the Holokaust in Ukraine, it is rather a strategy of displacing trauma and guilt or emphasizing the contribution of Ukrainians to saving Jews. The post-Soviet model also goes without a narrative about the Holokaust, but rather because of the lack of tradition in the USSR of describing war as a multi-ethnic experience. In this sense, both models are similar–both are mono-ethnic narratives. The minority discourse (ethnic model) about the Holokaust in Ukraine has not yet advanced to the rank of a nationwide narrative.
Models of memory about the Holokaust in Ukraine in the context of marginality and marginalization of memory discoursec
Keywords: Holokaust; Ukraina; pamięć; narracje; historiografia; polityka historyczna; postpamięć; Holocaust; Ukraine; memory; narratives; historiography; memory politics; post-memory